Skizofrenia dalam Film Joker (2019): Skizoanalisis Perspektif Deleuze dan Guattari - Andreas, Rino (UI Scholars Hub, 2021)
In medical-psychology, schizophrenia is defined as a severe psychotic disorder that causes its sufferers to experience hallucinations and chaotic behaviors. However, the paradigm of schizoanalysis considers schizophrenia as a system of thought that opposes the existence of established discourses (i.e. the Oedipus System). One form of schizophrenia can be seen in the Joker movie (2019). This research aims to identify the schizophrenia suffered by Arthur Fleck, the movie’s main character, from the schizoanalysis perspective as proposed by Gilles Deleuze and Felix Guattari. This qualitative research applied the interpretative description method based on the schizoanalysis perspective. This research found that the Joker character, as a schizophrenic, successfully reconstructs established ideas in his own ways solely through his desires. Joker unleashes his desires through practices presented as a form of resistance to the established system in Gotham City. This “madness” character was displayed by Arthur Fleck who opposes prevailing social values and norms, which he had previously imagined and questioned. However, he ends up destroying a greater system or order. Joker, as a progressive and revolutionary schizophrenic subject, clearly shows how a person can deconstruct the Oedipus to turn it into a counter-ammunition. Furthermore, the movie also shows that the broader “Joker movement” is disorganized as much as it is unplanned, spontaneous, and creative. Such spontaneity and creativity generates the flow of energy which stimulates those demonstrators to take a fight against capitalism.